Analysis of single, cisplatin‐induced DNA bends by atomic force microscopy and simulations. Issue 10 (3rd June 2018) - Dutta, Samrat; Rivetti, Claudio; Gassman, Natalie R.; Young, Carl G.; Jones, Bradley T.; Scarpinato, Karin; Guthold, Martin
Abstract: Bent DNA, or DNA that is locally more flexible, is a recognition motif for many DNA binding proteins. These DNA conformational properties can thus influence many cellular processes, such as replication, transcription, and DNA repair. The importance of these DNA conformational properties is juxtaposed to the experimental difficulty to accurately determine small bends, locally more flexible DNA, or a combination of both (bends with increased flexibility). In essence, many current bulk methods use average quantities, such as the average end‐to‐end distance, to extract DNA conformational properties; they cannot access the additional information that is contained in the end‐to‐end distance distributions. We developed a method that exploits this additional information to determine DNA conformational parameters. The method is based on matching end‐to‐end distance distributions obtained experimentally by atomic force microscopy imaging to distributions obtained from simulations. We applied this method to investigate cisplatin GG biadducts. We found that cisplatin induces a bend angle of 36° and softens the DNA locally around the bend. Abstract : We developed a method to determine DNA bends and DNA flexibility. The method is based on matching DNA end‐to‐end distance distributions obtained experimentally by AFM imaging (red bars) to distributions obtained from simulations (blue line). We applied this method to investigate cisplatin GG biadducts and found that cisplatin induces a bend angle of 36° at the GG biadduct and softens the DNA locally around the bend.